Winnie the Pooh : two favourite stories - Milne, A. A (Loughborough Ladybird)
Two stories about Winnie the Pooh and his antics: in the first, Pooh finds a honey tree and decides to climb it but quickly meets some very angry bees; in the second, Pooh visits Piglet in a beech tree but something quite unexpected happens as both of them are blown into a blustery adventure.
Include Colour Illustrations
Keywords: Winnie the Pooh and the honey tree -- Winnie the Pooh and the blustery day